COLLECTIVE ISLAMIC PRACTICES AND NATIONAL SOLIDARITY: RECONTEXTUALIZING KH AHMAD SANUSI’S EXEGESIS IN CONTEMPORARY INDONESIA - Ummi Kultsum; Lutfi (Penamas, 2025)
This article explores KH Ahmad Sanusi’s Qur’anic exegesis as a foundation for collective Islamic practices that strengthen national solidarity in contemporary Indonesia. Drawing on his interpretations of key verses, the study situates Sanusi’s thought within the historical context of struggles against colonialism and the present challenges of identity politics, digital disinformation, and eroding social trust. Through a qualitative analysis that combines contextual hermeneutics and comparative synthesis, the research demonstrates that Sanusi advocates for unity as an ethical imperative, manifest in shared rituals, communal discipline, and a collective commitment to moral renewal. Unlike state-led moderation that often emphasizes procedural tolerance, his exegesis emphasizes transforming individual dispositions and sustaining solidarity through religious ethics. While this approach provides profound insights into fostering cohesive civic identities, it faces limitations in adapting to pluralistic frameworks and decentralized authority. By integrating classical tafsir with contemporary sociopolitical analysis, this article contributes an interdisciplinary perspective on collective religious practices as a resource for resilient national cohesion.